Exploring the Elements of Organizational Inertia and Impactson Organization - SuhaimiMohd Yusof, Muhammad; Rahim Romle, Abd (International Journal of Psychosocial Rehabilitation, 2020)
Previous studies on inertia indicated the word of inertia in Latin means “idle and lazy” and it is always referred to describe difficulties faced by organizational in implementing changes within organization. As inertia became a part of the routines in the organization, the organization tended to practice the same routines and resisted changes due to their past experience. Inertia is a form of inability to resist changes either in processes or procedures within an organization, and it could be either individual or organizational. Literature reviews explained the development of organizational inertia, elements, and impacts on organizations.